Implementation of Norway's Food Security Policy: A Review of Strategies for Achieving Food Security in Indonesia - Alifa Semendawai, Farras; Sri Sundari; Suwito , Suwito (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Food security is a global issue that is increasingly urgent to be resolved along with world population growth, urbanization, and climate change. Norway, as a developed country with an efficient and innovative agricultural system, has become an exemplary example of achieving food security. On the other hand, Indonesia still faces many challenges in achieving optimal food security. In this context, this research reviews strategies for achieving food security in Indonesia and the implementation of Norway's food security policy. The literature study method was used to collect relevant information, and the results showed that the third strategy, which focuses on "ends," is the key to increasing food security. This strategy includes increasing national food independence, developing inclusive food supply chains, and increasing resilience to climate change and natural disasters. By considering strategies that have proven effective in Norway, Indonesia can identify concrete steps to increase food security in a sustainable manner.